The Importance of "Love" in Authentic Decolonization Work and SoTL Practice - Gariepy, Courtney; Bjartveit, Carolyn (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2023)
The definition of “decolonization” is contextual and relational, and it holds multiple meanings (de Oliveira Andreotti et al., 2015; Battiste, 2013; Smith, 2012), but it is seldom associated with the term “love.” This article explores how creating “ethical spaces” (Ermine, 2007) for engagement with Indigenous partners and community organizations has helped Bachelor of Child Studies (BCST) students at Mount Royal University (MRU) to understand the deeper meaning of decolonization and its connection to love in the context of academic and professional practices. During the 2021/22 academic year, four students collaborated with their professor and a community partner, Wee Wild Ones (WWO), a nature-inspired school, on decolonizing the organization’s early childhood education curriculum. The teachings of Elders and knowledge holders at MRU and within the wider community challenged the students’ understanding of decolonization and shifted their focus from an efficiency driven, goal-directed project approach towards building authentic relationships rooted in love, respect, and inclusivity. This article explores the meaning and role of love in the context of student-community partnerships, decolonization work, and scholarship of teaching and learning (SoTL) practice.